2009
DOI: 10.1021/jp901717h
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Evolution of Neodymium Boride Nanostructure Growth by Chemical Vapor Deposition

Abstract: Nanoscale-driven design of electron emission materials can significantly increase their overall efficiency as cathodes for field-induced electron emission by taking advantage of the field enhancement effect. The refractory nature and low work function (1.6 eV) of neodymium hexaboride (NdB 6 ) suggest that high aspect ratio NdB 6 nanostructures are potential candidates as efficient field emission cathodes. Here we report the morphological evolution of one-dimensional neodymium boride nanostructures synthesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…For potential application in cathode materials, the chemical vapor deposition (CVD) method for the synthesis of one-dimensional hexaborides have been reported intensively in the recent years. Rare-earth halides or alkaline-earth oxides powders were commonly chosen to react with BCl 3 , 5,17 B 2 H 6 , 18-20 B 10 H 14 , 21,22 or nido-pentaborane (or nido-decaborane) 2 at temperatures ranging from 800 to 1150 C. Recently, a similar method was applied to prepare one-dimensional hexaborides by rare-earth or alkaline-earth metals and BCl 3 via a CVD process, however, the reactants are either sensitive to water or rather toxic. [23][24][25][26][27] Therefore, it is necessary to explore an alternative route for the preparation of crystalline RB 6 and AB 6 by using convenient chemicals via simple processes at mild temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…For potential application in cathode materials, the chemical vapor deposition (CVD) method for the synthesis of one-dimensional hexaborides have been reported intensively in the recent years. Rare-earth halides or alkaline-earth oxides powders were commonly chosen to react with BCl 3 , 5,17 B 2 H 6 , 18-20 B 10 H 14 , 21,22 or nido-pentaborane (or nido-decaborane) 2 at temperatures ranging from 800 to 1150 C. Recently, a similar method was applied to prepare one-dimensional hexaborides by rare-earth or alkaline-earth metals and BCl 3 via a CVD process, however, the reactants are either sensitive to water or rather toxic. [23][24][25][26][27] Therefore, it is necessary to explore an alternative route for the preparation of crystalline RB 6 and AB 6 by using convenient chemicals via simple processes at mild temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…8 Thus, a lot of relevant research has been carried out on this kind of material with nanostructure attributes, especially on the low work function of REB 6 . [13][14][15] Problems are also found using this method. 9-12 While on account of the severe hygroscopicity of RCl 3 in even low degrees of moisture circumstances, it's difficult to obtain large-scale, high quality RB 6 nanowires through this method.…”
Section: Introductionmentioning
confidence: 99%
“…Brewer et al used RECl 3 and B 10 H 14 as rare earth metal and boron sources, respectively, together with palladium (Pd) nanoparticles to serve as catalysts, using a similar CVD process. [13][14][15] Problems are also found using this method. In addition to the semblable issues that exist for RECl 3 , the solid precursor B 10 H 14 , which is not easy to control in the CVD flow, also hinders the synthesis of REB 6 .…”
Section: Introductionmentioning
confidence: 99%
“…12 If single-crystalline NdB 6 nanostructures with high aspect ratio morphology, such as nanowires or nanotubes, can be fabricated, it may be an ideal candidate for the investigation and development of advanced eld emission theory, and efficient cathodes for vacuum electronic devices. Recently, Wang developed a palladium-nanoparticle-catalyzed chemical vapor deposition (CVD) method to synthesize NdB 6 nanoobelisks and nanowires, 13 but the boron precursor (B 10 H 14 ) was toxic and the Pd-Nd-B alloy drops on the tips would limit the electron emission and reduce the current density. 14 Very recently, Xu et al reported the synthesis of NdB 6 nanowires and nanoneedles via a catalyst-free CVD approach.…”
Section: Introductionmentioning
confidence: 99%